2001
DOI: 10.2135/cropsci2001.1946
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Meadow Fescue Accessions under Management‐Intensive Grazing

Abstract: Meadow fescue (Festuca pratensis Huds.) is a pasture grass that has been little used in North America since the introduction of its higher yielding relative, tall fescue (F. arundinacea Schreb.). The objectives of this study were to quantify genotypic variation for traits related to performance under management‐intensive grazing (MIG) within the USDA‐NPGS collection of meadow fescue accessions, to relate that variation to the geographic sources, and to compare these meadow fescue accessions to a range of tall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…Those seeding rates, however, were much greater than typically used on farms in north‐eastern USA. In 2007, seeding rates were decreased to reflect those common in farm practice in this region (Casler and Goodwin, 1998; Casler and Van Santen, 2001). Even though seeding rates were reduced greatly (8000 to 500 seeds m −2 ), there was a relatively small change in tiller density between years (proportionately 0·22 greater in 2006 than in 2007, averaged across all grass species).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those seeding rates, however, were much greater than typically used on farms in north‐eastern USA. In 2007, seeding rates were decreased to reflect those common in farm practice in this region (Casler and Goodwin, 1998; Casler and Van Santen, 2001). Even though seeding rates were reduced greatly (8000 to 500 seeds m −2 ), there was a relatively small change in tiller density between years (proportionately 0·22 greater in 2006 than in 2007, averaged across all grass species).…”
Section: Discussionmentioning
confidence: 99%
“…, 2009). In 2007, the seeding rate was reduced to match actual practice in north‐eastern USA pastures (Casler and Goodwin, 1998; Casler and Van Santen, 2001). A temporary grid consisting of 25 mm × 25 mm cells was placed on the soil surface to ensure uniform distribution of seeds.…”
Section: Methodsmentioning
confidence: 99%
“…Within the last decade, there has been a resurgence in meadow fescue utilization in temperate regions of the United States due to the release of improved cultivars from European breeding programs and research that documented beneficial traits compared with tall fescue from a livestock perspective. Casler and co‐workers (Casler et al, 1998, Casler and van Santen, 2001) reported that meadow fescue had superior apparent DM intake by grazing cattle compared with tall fescue, and concluded that the greatest potential utility for this grass is in managed intensive grazing systems. An additional advantage is that the nutritive value of meadow fescue is typically greater than that of most temperate grasses (Brink et al, 2007).…”
mentioning
confidence: 99%
“…Holstein cows and heifers were used to graze the plots in 1997 and 1998, after which the 10 accessions with the highest net herbage accumulation over a total of 10 grazing events were selected for advancement in the breeding program. Each of these accessions had net herbage accumulation higher than any of the 10 tall fescue check cultivars included in the experiment (Casler and van Santen, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…The 10 original Russian accessions from which Azov was selected had an average net herbage accumulation 8.4% greater than the average of 10 tall fescue cultivars evaluated under grazing at Arlington (Casler and van Santen, 2001). The apparent intake by grazing heifers and cows was 24.6% higher for these accessions compared with the tall fescue cultivars.…”
Section: Characteristicsmentioning
confidence: 99%